Regulation of Inflammation in Cancer by Eicosanoids - Greene, Emily R. (2011)
Inflammation in the tumour microenvironment is now recognized as one of the hallmarks of cancer. Endogenously produced lipid autacoids, locally acting small molecule lipid mediators, play a central role in inflammation and tissue homeostasis, and have recently been implicated in cancer. A well-studied group of autacoid mediators that are the products of arachidonic acid metabolism include: the prostaglandins, leukotrienes, lipoxins and cytochrome P450 (CYP) derived bioactive products. These lipid mediators are collectively referred to as eicosanoids and are generated by distinct enzymatic systems initiated by cyclooxygenase (COX 1 and 2), lipoxygenases (5-LOX, 12-LOX, 15-LOXa, 15-LOXb), and cytochrome P450s, respectively. These pathways are the target of approved drugs for the treatment of inflammation, pain, asthma, allergies, and cardiovascular disorders. Beyond their potent anti-inflammatory and anti-cancer effects, non-steroidal anti-inflammatory drugs (NSAIDs) and COX-2 specific inhibitors have been evaluated in both preclinical tumor models and clinical trials. Eicosanoid biosynthesis and actions can also be directly influenced by nutrients in the diet, as evidenced by the emerging role of omega-3 fatty acids in cancer prevention and treatment. Most research dedicated to using eicosanoids to inhibit tumor-associated inflammation has focused on the COX and LOX pathways. Novel experimental approaches that demonstrate the anti-tumor effects of inhibiting cancer-associated inflammation currently include: eicosanoid receptor antagonism, overexpression of eicosanoid metabolizing enzymes, and the use of endogenous anti-inflammatory lipid mediators. Here we review the actions of eicosanoids on inflammation in the context of tumorigenesis. Eicosanoids may represent a missing link between inflammation and cancer and thus could serve as therapeutic target(s) for inhibiting tumor growth.